A Low-Power Air Quality Monitoring System Based on the TI MSP430 Microcontroller Family: Design and Experimental Evaluation - Michael Atoran (Athallah Publishing, 2026)
Air pollution has become a critical environmental and public health issue, necessitating the development of efficient, reliable, and energy-efficient monitoring systems. This study presents the design and experimental evaluation of a low-power air quality monitoring system based on the Texas Instruments MSP430 microcontroller family. The proposed system integrates gas sensors for detecting key air pollutants, a microcontroller unit for data processing, and display and alert modules for real-time user notification. The MSP430 microcontroller is selected due to its ultra-low power consumption and suitability for continuous environmental monitoring applications. The system architecture is designed using a modular approach, consisting of sensor, processing, display, and warning modules to ensure flexibility and scalability. Experimental evaluation was conducted to assess system performance in terms of power consumption, data accuracy, response time, and operational reliability. The results demonstrate that the proposed system achieves significant energy efficiency while maintaining acceptable accuracy and responsiveness for real-time monitoring. The implementation of power management strategies, including low-power modes and optimized data acquisition, further enhances system performance and prolongs operational lifespan.